The Role of Islamic Religious Education Teachers in Addressing Students’ Moral Crisis - Yusuf, M.; Pabelan, Dedek; Tifani, Naila; Alfenita, Siska; Yanti, Novia; Nursyamsi, Nursyamsi (STIT Ahlussunnah Bukittinggi, 2025)
The purpose of this study is to examine the role of Islamic religious education teachers in addressing the moral crisis faced by junior high school students in Indonesia. This type of research employs a qualitative approach with a case study design. The results of this problem are the role of Islamic religious education teachers in addressing students' moral crisis by being good role models, spreading Islamic values ​​through interesting ways such as storytelling and setting an example, and providing ongoing moral direction and guidance. This task includes building positive character through daily interactions, helping students overcome their moral problems, and ensuring that Islamic religious education lessons are directly related to their lives. The factors that cause the moral crisis at the junior high school level include the impact of the family (minimal character education, poor parenting, and family economic conditions), the social environment (peer influence, wrong associations, and community conditions that do not support education), and technology (the negative impact of gadgets and social media). In addition, internal aspects such as a lack of understanding of moral and ethical values ​​and a lack of positive role models from teachers and parents also contribute. The moral crisis among adolescents is one of the main challenges faced by modern society today. Amidst technological advances, the influence of globalization, and changes in social values, adolescent morality is increasingly exposed to negative external influences. Rapid lifestyle changes, particularly due to widespread access to social media and global culture, have given rise to various moral issues.